2022
DOI: 10.1038/s41525-021-00267-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural variation analysis of 6,500 whole genome sequences in amyotrophic lateral sclerosis

Abstract: There is a strong genetic contribution to Amyotrophic lateral sclerosis (ALS) risk, with heritability estimates of up to 60%. Both Mendelian and small effect variants have been identified, but in common with other conditions, such variants only explain a little of the heritability. Genomic structural variation might account for some of this otherwise unexplained heritability. We therefore investigated association between structural variation in a set of 25 ALS genes, and ALS risk and phenotype. As expected, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…We analyzed the carriage of NEFH alleles, taking into account the site of disease onset. Although the survival trajectories for spinal and bulbar onset patients did not differ within this cohort, it is important to include this covariate since short structural variants have previously been shown to stratify sALS patient sub-phenotype [33][34][35] . In the present study, no signi cant associations were detected between NEFH alleles and survival.…”
Section: Discussionmentioning
confidence: 97%
“…We analyzed the carriage of NEFH alleles, taking into account the site of disease onset. Although the survival trajectories for spinal and bulbar onset patients did not differ within this cohort, it is important to include this covariate since short structural variants have previously been shown to stratify sALS patient sub-phenotype [33][34][35] . In the present study, no signi cant associations were detected between NEFH alleles and survival.…”
Section: Discussionmentioning
confidence: 97%
“…The variant caller used in this study detected multiple classes of SVs, however, small inversions and insertion/deletions < 200 bp could not be analyzed by the Manta platform [27]. Further investigation into variants outside of the know ALS genes in addition to wet lab validation is required to gain a holistic understanding of the contribution of genetic variation to ALS risk and phenotype [27].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, another recent study has investigated SVs in 6580 whole genome sequences (4315 ALS and 1880 controls) from the Project MinE cohort to determine genotype-phenotype correlations in known ALS genes. Al Khleifat, Iacoangeli [27] reported that structural variants in C9orf72 (repeat expansion), Valosin containing protein VCP (inversion) and erb-b2 receptor tyrosine kinase 4, ERBB4 (deletion) are variously associated with ALS disease risk and phenotype. The variant caller used in this study detected multiple classes of SVs, however, small inversions and insertion/deletions < 200 bp could not be analyzed by the Manta platform [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis of known ALS-causing genes demonstrated a role for structural variants in this subset of genes. 6 Specifically, genomic structural variants in C9orf72 , valosin-containing protein ( VCP ) and Erb-B4 receptor tyrosine kinase 4 ( ERBB4 ) genes were shown to modify ALS risk, age, and site of onset as well as progression and survival, highlighting the role of structural variants in ALS pathogenesis. 6 Similarly, repeat expansions, which are one type of structural variation, in the C9orf72 gene as well as the medium CAG repeat in the ataxin 2 ( ATXN2 ) gene can cause ALS.…”
Section: Introductionmentioning
confidence: 99%